Proximate analysis and antimicrobial activity of cultivated macrolepiota dolichaula strain MFLUCC-13-0579 - Rizal, Leela Maya; Hyde, Kevin D; Chukeatirote, Ekachai; Kakumyan, Pattana; Chamyuang, Sunita (Asia-Pacific Journal of Science and Technology, 2016)
Macrolepiota dolichaula, an edible white spored gilled mushroom, is widely distributed in tropical and temperate countries. In this study, nutritional quality of M.dolichaula strain MFLUCC-13-0579 cultivated in compost was investigated. Proximate analysis of dry weight of M. dolichaula showed a composition of 25.53% protein, 44.37% carbohydrate, 14.17% fiber, 1.17 % lipid and 5.19% ash with energy of 299.06 kJ/g mushroom. In addition, the antimicrobial activities from fresh mushroom, dry mushroom and mycelial extracts showed significant activities against Micrococcus luteus and Staphylococcus aureus. Based on this study, it can be concluded that M. dolichaula is a good source of nutrients and posses some antimicrobial activities.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">